The capability of NOTHAS in the prediction of extreme weather events across different climatic areas - Spiridonov, Vlado; Grcić, Marija; Sladić, Nedim; Ćurić, Mladjen; Jakimovski, Boro (Springer International Publishing, 2023)
Climate changes are accelerating and leading to climate and weather extremes with the most destructive impacts and negative consequences on the planet. For these reasons, precise forecasting, and announcement of weather disasters of a convective nature, from local to synoptic scales, is very important. The Novel Thunderstorm Alert System (NOTHAS) has shown outstanding results in forecasting and early warning of different modes of convection, including local hazards in mid-latitudes. In this study, an attempt has been made to apply this tool in the prediction of different atmospheric systems that occur in different climatic regions. The upgraded prognostic and diagnostic algorithm with adjusted complex parameters and criteria representative of tropical storms and tropical cyclones showed good coincidence with the available observations. NOTHAS showed skill and success in assessing the dynamics and intensity of Hurricane Ian, which hit the west coast of Florida on 30 September 2022 and caused great material damage and human losses. This advanced tool also detected the most intense-extreme Level-5 on 1 September 2021, over New York, when catastrophic flooding occurred within the remnants of Hurricane Ida. Likewise, the upgraded model configuration very correctly predicted the trajectory, modifications, and strength of super typhoon Nanmadol over Japan (19 September 2022), 24–48 h in advance, and super typhoon Noru over the Philippines (25 September 2022). The system showed the temporal and spatial accuracy of the location of the heavy rainfall and flash flood. In general, the obtained results for all evaluated cases are encouraging and provide a good basis for further testing, verification, and severe weather warnings and guidance for weather services worldwide.
Keywords: Weather and climate extremes, WRF-model forecast, Diagnostic tool, Convective weather alert, Tropical cyclone